Take My Yoke and Learn of Me: Matthew 11:28-30 and Hospitality in Theological Education in Indonesia - Bakhoh Jatmiko; I Putu Ayub Darmawan; Rebecca Joy Guild (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
This research was motivated by the situation of theological education in Indonesia, which still perpetuates traditional models of education, where learning still tends to be one-way, authoritative, and more focused on cognitive-academic development with “a rote learning approach.” This has left learners (a group of learners) alienated, marginalised, and even feeling pressured in the learning process. This condition makes it difficult to provide theological education that is hospitable and transformative in the lives of learners. Meanwhile, the Bible has shown that hospitality is an important theme in both the Old and New Testaments. God is a hospitable God and offers hospitality to his people. According to the author, hospitality also needs to be presented in theological education in Indonesia. From the theoretical framework of hospitality and theological education, the author analyses Matthew 11:28-30 to find the principles of hospitality relevant to theological education in Indonesia. The author examines various thoughts on hospitality through a literature study. The selected text was studied using an exegetical approach and inductive interpretation. Based on the analysis, it was found that Jesus' learning environment differs from that of the Scribes. Jesus' learning environment is inclusive, liberating and collaborative. The implication is that theological education with hospitality provides a learning atmosphere that is liberating, uplifting, takes into account the uniqueness of the students, and provides a comfortable atmosphere.